2021
DOI: 10.12659/msm.929389
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hydrogen Sulfide with Femoral Bone Mineral Density in Osteoporosis Patients: A Preliminary Study

Abstract: Background Accumulated evidence has suggested that hydrogen sulfide (H 2 S) has a role in bone formation and bone tissue regeneration. However, it is unknown whether the H 2 S content is associated with bone mineral density (BMD) in patients with osteopenia/osteoporosis. Material/Methods In the present study, we aimed to explore the changes of serum H 2 S in osteopenia and osteoporosis pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“… 4 In patients with osteoporosis, the expression of CBS was found to be down-regulated in femur tissues, leading to a lower BMD. 5 These findings support the idea that DNA methylation-related enzymes, including ALOX12 and CBS, are important for the occurrence of osteoporosis. However, the specificities in these 2 genes of osteoporosis human samples are largely unclear.…”
supporting
confidence: 71%
“… 4 In patients with osteoporosis, the expression of CBS was found to be down-regulated in femur tissues, leading to a lower BMD. 5 These findings support the idea that DNA methylation-related enzymes, including ALOX12 and CBS, are important for the occurrence of osteoporosis. However, the specificities in these 2 genes of osteoporosis human samples are largely unclear.…”
supporting
confidence: 71%
“…Together, this information leads us to hypothesize that AA, having naturally decreased vitamin D and H 2 S levels, leads to decreased adiponectin, resulting in increased BMD via decreased osteoclast activity (Figure 6). Hao et al recently reported an inverse association between H 2 S levels and bone health [88], thus providing further support for this hypothesis. However, reports of opposite measures have also been reported [89][90][91]; as a result, more research needs to be conducted on this topic to see if it potentially explains the vitamin D/BMD paradoxical relationship.…”
Section: Our Third Novel Hypothesis: Could Racial Differences In Hydr...mentioning
confidence: 58%
“…Accumulated evidence has suggested that hydrogen sulfide (H 2 S) plays a significant role in bone formation and bone tissue regeneration. Interestingly, it was reported that the serum levels of H 2 S were unexpectedly increased in patients with osteoporosis [ 31 ]. In contrast, the abundance of Rothia and Turicibacter were significantly reduced in the model group compared to the normal group.…”
Section: Resultsmentioning
confidence: 99%